The power of numbers: Supporting community groups to establish market-oriented opportunities - International Livestock Research Institute (International Livestock Research Institute, 2019)
The Accelerated Value Chain Development (AVCD) program has been supporting dairy cooperatives and other producer organizations to become more commercially oriented by adopting a ‘dairy business hub’ model. This video shows how through training in governance, financial management and strategic and business planning, AVCD has encouraged dairy farmer groups to aggregate, which is enabling individual farmers to sell more of their milk. These groups now appreciate the business approach to agriculture. For more information about the AVCD program visit www.avcdkenya.net